A prospective, matched comparison of ultra‐low and standard‐dose computed tomography for assessment of renal colic. (23rd June 2020) - Roberts, Matthew J.; Williams, Julia; Khadra, Sam; Nalavenkata, Sunny; Kam, Jonathan; McCombie, Steve P.; Arianayagam, Mohan; Canagasingham, Bertram; Ferguson, Richard; Khadra, Mohamed; Varol, Celi; Winter, Matthew; et al.
Abstract : Objective: To determine the diagnostic accuracy of ultra‐low‐dose computed tomography (ULDCT) compared with standard‐dose CT (SDCT) in the evaluation of patients with clinically suspected renal colic, in addition to secondary features (hydroureteronephrosis, perinephric stranding) and additional pathological entities (renal masses). Patients and methods: A prospective, comparative cohort study was conducted amongst patients presenting to the emergency department with signs and symptoms suggestive of renal or ureteric colic. Patients underwent both SDCT and ULDCT. Single‐blinded review of the image sets was performed independently by three board‐certified radiologists. Results: Among 21 patients, the effective radiation dose was lower for ULDCT [mean (SD) 1.02 (0.16) mSv] than SDCT [mean (SD) 4.97 (2.02) mSv]. Renal and/or ureteric calculi were detected in 57.1% (12/21) of patients. There were no significant differences in calculus detection and size estimation between ULDCT and SDCT. A higher concordance was observed for ureteric calculi (75%) than renal calculi (38%), mostly due to greater detection of calculi of <3 mm by SDCT. Clinically significant calculi (≥3 mm) were detected by ULDCT with high specificity (97.6%) and sensitivity (100%) compared to overall detection (specificity 91.2%, sensitivity 58.8%). ULDCT and SDCT were highly concordant for detection of secondary features, while ULDCT detected less renal cysts of <2 cm. Inter‐observer agreement for the ureteric calculi detection was 93.9% for SDCT and 87.8% for ULDCT. Conclusion: ULDCT performed similarly to SDCT for calculus detection and size estimation with reduced radiation exposure. Based on this and other studies, ULDCT should be considered as the first‐line modality for evaluation of renal colic in routine practice.